2016
DOI: 10.1530/rep-15-0340
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases 2 and 9 and MMP9/NGAL complex activity in women with PCOS

Abstract: It is believed that matrix metalloproteinases (MMPs) play important roles in follicular development and pathogenesis of polycystic ovary syndrome (PCOS). However, conflicting results are available about the alteration of MMP2 and MMP9 concentrations or activities in PCOS. In fact, there is no study entirely investigating both concentration and activity of these MMPs and serum levels of their tissue inhibitors TIMP2 and TIMP1, as well as lipocalin-bound form of MMP9 (MMP9/NGAL). Therefore, the thoroughness of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…Secondly, in the present study we quantified free MMP‐9 levels that is both pro‐MMP‐9 and active MMP‐9 levels. However, we have not measured MMP‐9/NGAL complex concentrations, which is believed to have an additive functional affect . Anticoagulants used for collection of blood samples were shown to altered activity of MMP‐9 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Secondly, in the present study we quantified free MMP‐9 levels that is both pro‐MMP‐9 and active MMP‐9 levels. However, we have not measured MMP‐9/NGAL complex concentrations, which is believed to have an additive functional affect . Anticoagulants used for collection of blood samples were shown to altered activity of MMP‐9 .…”
Section: Discussionmentioning
confidence: 92%
“…However, we have not measured MMP-9/ NGAL complex concentrations, which is believed to have an additive functional affect. 28 Anticoagulants used for collection of blood samples were shown to altered activity of MMP-9. 29 In the current report, we have used EDTA as anticoagulant and samples collected in EDTA has been shown optimal activity of both pro and mature MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Ranjbaran et al in 2016 was the rst one on the involvement of the activity of MMP-9 in pathogenesis of PCOS. They showed that the serum level of MMP-9 was signi cantly higher in women with PCOS compared to the control group (42). The study of Dambala et al in 2017 also showed the same result (43).…”
Section: Discussionmentioning
confidence: 78%
“…Tokmak et al, also reported the similar results [16] . While Ranjbaran et al, reported that a noticeable decline in FSH and an increase in LH levels together with a significant increase in LH/FSH ratio were found in PCOS patients [19] .…”
Section: Discussionmentioning
confidence: 94%